2021
DOI: 10.1177/1941738120970956
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Consequences of Sport Specialization Among Little League Baseball Players

Abstract: Background: Baseball is one of the most popular boy’s youth sports, and there has been a rise in the rates of certain overuse injuries among players. Specialization has been identified as a risk factor for overuse injury in high school athlete populations, but there is little understanding of the prevalence or consequences of sport specialization in Little League baseball players. Hypothesis: Sport specialization will be highly prevalent among Little League baseball players and specialization will be associate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 34 publications
1
15
0
Order By: Relevance
“…Moreover, the findings are contrary to several studies which demonstrated associations between specialization and injury. 32,37 Girls specialized earlier than boys, which was consistent with findings from a recent study of NCAA (National Collegiate Athletic Association) athletes. 38 A larger sample size, with a larger percentage of girls and a broader range of competitive levels will provide a better assessment of the impact of early specialization on these relationships and potentially illuminate the motivating factors behind these trends.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Moreover, the findings are contrary to several studies which demonstrated associations between specialization and injury. 32,37 Girls specialized earlier than boys, which was consistent with findings from a recent study of NCAA (National Collegiate Athletic Association) athletes. 38 A larger sample size, with a larger percentage of girls and a broader range of competitive levels will provide a better assessment of the impact of early specialization on these relationships and potentially illuminate the motivating factors behind these trends.…”
Section: Discussionsupporting
confidence: 90%
“…Moreover, the findings are contrary to several studies which demonstrated associations between specialization and injury. 32 , 37 …”
Section: Discussionmentioning
confidence: 99%
“…Croci et al (14) identified those college baseball players who had highly specialized by 13 years were more likely to have a history of upper extremity injury than players who were low/moderate specialization and reported worse subjective throwing arm function. This has been observed in the Little League population and high school population, as well as with players of high sport specialization demonstrating worse throwing arm health compared with low-specialization players (15,16).…”
Section: Literature Reviewmentioning
confidence: 84%
“…A number of studies have looked at factors related to injury in the youth baseball population over the past year ranging in topics from; early sport specialization (ESS) (12)(13)(14)(15)(16), pitch counts (17)(18)(19)(20)(21)(22)(23), prethrowing protocols (24,25), imaging findings (26), to body region-specific inquiries (27)(28)(29)(30)(31)(32)(33)(34)(35)(36)(37)(38)(39)(40)(41)(42)(43) in search for opportunities to reduce the risk of injury in this population. We will review a wide range of articles and their relevance to injury risk in this population.…”
Section: Literature Reviewmentioning
confidence: 99%
“…25 Research has indicated that high-level specialization in Little League baseball players is relatively low; however, year-round play and receiving private coaching were more common. 22 The increased exposure and stress can contribute to both chronic and acute injuries. Most literature has focused on evaluating relationships between specialization and injury at a single time point.…”
mentioning
confidence: 99%